2000
DOI: 10.1073/pnas.260503597
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an intracellular protease fromPyrococcus horikoshiiat 2-Å resolution

Abstract: The intracellular protease from Pyrococcus horikoshii (PH1704) and PfpI from Pyrococcus furiosus are members of a class of intracellular proteases that have no sequence homology to any other known protease family. We report the crystal structure of PH1704 at 2.0-Å resolution. The protease is tentatively identified as a cysteine protease based on the presence of cysteine (residue 100) in a nucleophile elbow motif. In the crystal, PH1704 forms a hexameric ring structure, and the active sites are formed at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 32 publications
5
133
1
Order By: Relevance
“…Structural Similarity of DJ-1 to Other Proteins-Comparison of the DJ-1 structure with the Protein Data Bank (18) data base using the DALI search engine (19) revealed that DJ-1 is structurally most similar to the monomer unit of protease I, an intracellular cysteine protease from Pyrococcus horikoshii with a Z score of 26.3 and a root mean square deviation of 1.6 Å for 166 residues (Fig. 4, a and b) (20). The DALI search also revealed that DJ-1 has similar topology to three proteins: the domain of catalase HPII from E. coli (17,21); the subunit of anthranilate synthase TrpG from Sulfolobus solfataricus (22,23); and the domain of GMP synthetase from E. coli (Table II) (24).…”
Section: Resultsmentioning
confidence: 99%
“…Structural Similarity of DJ-1 to Other Proteins-Comparison of the DJ-1 structure with the Protein Data Bank (18) data base using the DALI search engine (19) revealed that DJ-1 is structurally most similar to the monomer unit of protease I, an intracellular cysteine protease from Pyrococcus horikoshii with a Z score of 26.3 and a root mean square deviation of 1.6 Å for 166 residues (Fig. 4, a and b) (20). The DALI search also revealed that DJ-1 has similar topology to three proteins: the domain of catalase HPII from E. coli (17,21); the subunit of anthranilate synthase TrpG from Sulfolobus solfataricus (22,23); and the domain of GMP synthetase from E. coli (Table II) (24).…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with recent x-ray diffraction data (17,18), which also demonstrate dimer formation. Different members of the DJ-1 superfamily of proteins form many different types of oligomeric species, and this data suggest that DJ-1 is more structurally similar to the bacterial Hsp31, which forms dimers (16) and less like PH1704, which forms hexamers (25). Full-length DJ-1 is necessary for its self-interaction, suggesting a contribution of both N and C termini to the proper folding or self-interactions of the protein.…”
Section: Discussionmentioning
confidence: 96%
“…The in-gel protease assay was carried out as described previously for determining the protease activity of the PfpI family of proteases (34,35). Purified wild-type or mutant DJ-1 protein (1-100 g) was electrophoresed onto 12% SDS-polyacrylamide gels containing 0.1% co-polymerized gelatin under non-reducing conditions.…”
Section: Dj-1 Expressionmentioning
confidence: 99%
“…Protease-Since DJ-1 also shares significant sequence and structural homology with the PfpI family of intracellular proteases (23,35), we sought to determine whether DJ-1 possesses intrinsic protease activity. We first assessed the proteolytic activity of DJ-1 by using the same in-gel protease assay that was used to demonstrate the protease activity of PfpI and PH1704 (34,35).…”
Section: Dj-1 Functions As a Cysteinementioning
confidence: 99%
See 1 more Smart Citation